Investigating the influence of Enjoyment, Convenience, Trust, and Social influence on Perceived Usefulness and Intention to Use among Mobile Game Users - Azizah, Amiril; Putri, Rizky Septia Eka; Kintani, Anninda; Ardli, Fajrina Zaki; Rif’ah, Rif’ah; Dwisafira, Amelia (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
This study aims to analyze and establish the effects of enjoyment, convenience, trust, and social influence on perceived usefulness and intention to use among Mobile Game Users in Samarinda City. This study employs a quantitative approach, utilizing path analysis with IBM SPSS Statistics V23 and Structural Equation Modeling (SEM) software with IBM AMOS V5. A total of 180 respondents from various locations in Samarinda City participated in the study, and data was collected using a questionnaire distributed through the Snowball Sampling Method. The Likert scale with a range of 1-5 was utilized for measuring the variables. Validity and reliability tests, as well as estimation and structural model fit tests, were conducted to analyze the collected data. The findings, obtained through statistical analysis using SEM-AMOS version 5.0, indicate the following results: trust significantly influences the perceived usefulness of Mobile Game users. Enjoyment, convenience, and social influence significantly affect the perceived usefulness of Mobile Game users. Furthermore, enjoyment and convenience have a significant impact on the intention to use Mobile Game Users in Samarinda City. However, trust does not significantly affect social influence among Mobile Game Users in Samarinda City. Additionally, perceived usefulness demonstrates a significant effect on the intention to use Mobile Game Users. The results provide valuable insights into the factors influencing perceived usefulness and intention to use among Mobile Game Users in Samarinda City. Understanding the impact of enjoyment, convenience, trust, and social influence on these variables can assist in the development of strategies to enhance user experiences and encourage greater adoption and usage of mobile games. The findings of this study can be utilized by mobile game developers and marketers to optimize their offerings and improve user satisfaction and engagement. The findings of this study shows that a significant relationship between.